(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aimed to develop and measure the effectiveness of Moodle-based e-learning as a learning medium for vocational high school students. The study used a Research and Development (R&D) approach with the ADDIE model and a quasi-experimental quantitative design (one-group pretest–posttest). The population included all students from classes X DKV1, X DKV2, and X DKV3 at SMK Negeri 1 Luragung, with class X DKV2 serving as the sample. Questionnaires and tests were used as instruments to assess the LMS’s feasibility and effectiveness. The data were analyzed using quantitative descriptive methods. The results showed the medium received feasibility scores of 81.6% from students, 88% from media experts, and 98% from material experts, placing it in the "Highly Feasible" category. The learning effectiveness, measured by the N-Gain Score, averaged 0.738, indicating a "High" category. These findings demonstrate that Moodle e-learning is both feasible and effective in improving student understanding and learning outcomes, and is suitable for implementation as a digital learning model in vocational schools.